KEMAMPUAN PROFESIONALISME GURU DALAM MENDUKUNG PENERBITAN SURAT KABAR SEKOLAH - Ananda, Refisa; Hayati, Najmi; Zuve, Farel Olva; Satria, Dadi (STKIP Pesisir Selatan, 2021)
The school newspaper is a mass communication medium published and managed by the school. The main manager is OSIS who are accompanied by Indonesian Language teachers and Information and Communication Technology teachers under the supervision of the school principal. The existence of a school newspaper is very important as a place to accommodate student work. This activity producesan online school newspaper that can be accessed anywhere and from anywhere. The purpose of this training is to provide facilities and infrastructure that can be used by schools to support student literacy activities